2006
DOI: 10.1242/jcs.02999
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule plus-end loading of p150Glued is mediated by EB1 and CLIP-170 but is not required for intracellular membrane traffic in mammalian cells

Abstract: Summary Microtubule dynamics and function are regulated, at least in part, by a family of proteins that localize to microtubule plus-ends, and include EB1, CLIP-170 and the dynactin component p150Glued. Plus-end pools of these proteins, notably dynactin, have been invoked in a number of ‘search-and-capture’ mechanisms, including the attachment of microtubules to kinetochores during mitosis and to endomembranes prior to the initiation of intracellular transport. Here we show that, in mammalian cells, EB1 is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 41 publications
(84 reference statements)
9
85
0
Order By: Relevance
“…A second possibility (not mutually exclusive with the first) is that the two CAP-Gly domains endow CLIP-170 with the ability to bind simultaneously to tubulin and other CAP-Gly-binding proteins. One such protein is EB1 (18,35). Interestingly, it has been reported that EB1 has a higher affinity for CAP-Gly-1 than CAP-Gly-2 (33).…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility (not mutually exclusive with the first) is that the two CAP-Gly domains endow CLIP-170 with the ability to bind simultaneously to tubulin and other CAP-Gly-binding proteins. One such protein is EB1 (18,35). Interestingly, it has been reported that EB1 has a higher affinity for CAP-Gly-1 than CAP-Gly-2 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Both EB1 family proteins and XMAP215 can act independently as microtubule growth promoters, but in some instances they are linked by SLAIN motif family proteins, which strongly stimulate processive microtubule growth in interphase cells [van der Vaart et al, 2011]. The dyneindynactin complex can also access microtubule ends in both EB1-dependent and independent manners [Miller et al, 2006;Watson and Stephens, 2006]. It is noteworthy that n 608…”
Section: Molecules Involved In Microtubule End Positioningmentioning
confidence: 99%
“…In addition, dynactin plays other roles independently of microtubule motors, by facilitating attachment of microtubules to several subcellular structures. Although initial studies demonstrated that dynactin contributed to microtubule anchoring at the centrosome during interphase (15,16), recent results provided the first clues concerning its role as an initial receptor for cytoplasmic membrane vesicles at microtubule plus ends (17)(18)(19)(20), although this model has been brought into question (21).…”
mentioning
confidence: 99%